Effects of Atmospheric Corrosion on the Car Park Roof Structure - Vincent Kvocak; Renata Vargova; Pavol Beke; Eva Terpakova (Communications - Scientific letters of the University of Zilina, 2013)
The effects of the outdoor climatic conditions are observed in all constructions. Steel members of such constructions are affected negatively by urban atmospheres in a synergy with the effects of industrial pollutants. In very exposed buildings the impact of such effects is so significant that diagnostic assessment of their state and technical expertise is required.The paper presented shows the actual state assessment and the verification of structural reliability of the existing load-bearing structure of an exterior car park roof, emphasizing the estimation of corrosion losses in the steel structure that have considerably lowered its lifespan and obstructed its safe operation.